Two-stage robust estimators for product concentration in a penicillin fermentation - 396946 Chow, Ai Wei; Arshad Ahmad, 1963-; Symposium of Malaysian Chemical Engineers (17th : 2004 : Perak) (Skudai : Universiti Teknologi Malaysia, 2004)
50